Into the multi-omics era: Progress of T cells profiling in the context of solid organ transplantation - Zhi, Yao; Li, Mingqian; Lv, Guoyue (Frontiers in Immunology, 2023)
The biggest obstacle to long-term allograft survival is rejection, mostly mediated by T cells, which play a pivotal role in the adaptive immune system, offering protection against alloantigens and other pathogens. Three factors influence this effect: the diverse phenotypes of T cells, antigen specificities, and highly diverse T cell receptors (TCRs). TCR, a critical molecule on the surface of T cells, consists of somatically rearranged TCRα and TCRβ chains. Hence, the TCR repertoire in individuals is highly diverse, enabling the recognition of a wide range of foreign antigens. However, it is difficult to assess this recognition through traditional methods. Recently, with the widespread development of high-throughput sequencing technologies, several experimental and computational methods have emerged rapidly, enabling TCR identification, alloantigen specificities estimation, and TCRs combination with the genome, transcriptome, epigenome, and proteome at single-cell resolution. This review focuses on advances in these technologies and summarizes their application to improve the understanding of T-cell heterogeneity in solid organ transplantation.